2019
DOI: 10.1177/0892705719889985
|View full text |Cite
|
Sign up to set email alerts
|

The fatigue behavior of polymeric sulfur-modified asphalt mixtures subjected to freeze-thaw conditioning

Abstract: Abundance, affordability, and also the usability of sulfur as a part of the binder are the main reasons for using this additive in asphalt mixtures. However, lack of proper adhesion and brittle behavior of sulfur-modified asphalt mixtures could make them susceptible to moisture damage and fatigue cracking. In this regard, anti-stripping agents and some polymers like crumb rubber may be used to overcome these types of distresses. This research aimed at investigating the effects of polymeric sulfur and crumb rub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…A large number of laboratory findings showed that the freeze-thaw cycle significantly reduced the strength, fatigue life, and durability of different asphalt mixtures [5][6][7][8][9][10][11]. The technology of CT (Computed Tomography) scanning is used to study the freeze-thaw damage process of the asphalt mixture, which can effectively reveal the meso characteristics of the asphalt mixture during the freeze-thaw process in comparison with the general testing methods for mix design [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of laboratory findings showed that the freeze-thaw cycle significantly reduced the strength, fatigue life, and durability of different asphalt mixtures [5][6][7][8][9][10][11]. The technology of CT (Computed Tomography) scanning is used to study the freeze-thaw damage process of the asphalt mixture, which can effectively reveal the meso characteristics of the asphalt mixture during the freeze-thaw process in comparison with the general testing methods for mix design [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of works [ 1 , 2 , 3 , 4 , 5 , 6 ] have shown that the use of sulfur as a modifier for asphalt concrete is a promising direction, allowing the expansion of the temperature range of operation of asphalt concrete pavements in the area of high positive temperatures. In addition, in works [ 5 , 6 , 7 ] it is shown that the introduction of sulfur provides a decrease in the amount of bitumen in the asphalt concrete mixture, as well as a decrease in the temperature of preparation and laying The use of sulfur improves not only the operational properties of sulfur asphalt concrete (SEA) but also the technological properties of the mixture. Thus, in [ 8 ], the rheological properties of a bitumen-sulfur melt were investigated and it was shown that the introduction of sulfur significantly reduces the viscosity of such melts.…”
Section: Introductionmentioning
confidence: 99%
“…Hong et al [22] tested the dynamic modulus and mass loss of asphalt pavement in the cold region, evaluated the strain-stress behavior of the test piece, and analyzed its F-T durability. Kavussi et al [23] used rubber particles to modify asphalt mixture. On the basis of the response surface method, the influence of F-T cycles on water stability and fatigue performance was evaluated.…”
Section: Introductionmentioning
confidence: 99%